Cold atoms laboratory in a hollow core fiber - Leong, Wui Seng (Nanyang Technological University, 2021)
Coherent manipulation and interaction between atoms and light are the core ingredients in modern quantum science and technology. Various applications such as quantum computation, quantum memories and quantum sensors which are promising in future technologies, are currently under exploration. However, due to the diffraction nature of light, miniaturizing quantum systems involving atom-light interactions has been highly limited. To avoid diffraction, I load cold atoms into a hollow-core fiber (HCF) and demonstrate four major experiments inside the fiber: inertia-sensitive Mach-Zehnder atom interferometer, long-lived quantum spin coherence, light storage and creation of an array of Schr\"odinger cat states.